萌芽個案計畫---結合標靶及磁振造影之多功能磁性奈米藥物載體技術研發以增強乳癌腫瘤治療與監控(I) - 陳三元; CHEN San-Yuan (My University, 2012)
本技術開發出一種高生物相容性且兼具藥物療效及生物顯影功能的磁敏感奈米中 空球藥物載體，此種中空載體的合成，只需要單一兩性高分子與氧化鐵結合，當與油 相氧化鐵混和乳化之後，會自組裝成水-油-水的奈米中空球結構。氧化鐵除了可以穩定 油相外層，也是提供載體磁性的媒介。藉由控制高分子的分子量，便能夠控制載體的 大小，從數十奈米至數百奈米均可得到。經過專利搜尋，本研究所開發的技術具有相 當新穎的發明，無論是載體製程及結構功能性皆與現有專利不同，故具有極高專利性 及商業應用價值。磁性奈米藥物載體、磁引導與抗癌藥物控制釋放及結合標靶治療， 來達到治療乳癌的目的。本藥物載體不但可以提供低副作用性、減低整體投藥量、利 用體外刺激做定點投藥，還可以整合MR等顯影系統作疾病或是藥物釋放量的監測。

This nanocarrier can be synthesized in only one polymer incorporated with iron oxide nanoparticles, without the help of emulsifier and solvent. In the past, methods about forming double-emulsion hollow spheres need complicated polymerization, phase separation, or the use of co-polymer and rigid inorganics to stabilize the W/O (O/W) interface and shell. This new technique provides a much easier method to synthesize the double-emulsion hollow sphere. The synthesized carriers are very stable that they remained intact after several times centrifugation. Further, we can control the size of carriers from tens to hundreds of nanometer by changing the molecular weight of polymer. Based on the patent search, the technology developed in this study has a fairly new novelty and invention. The functions and structures of the patented carriers are different from the existing patent so that it can be applied as a new patent and also show high potential commercial applications. The novel multifunctional nanocarriers capable of integrating with magnetic guidance and target-chemotherapy has been designed and fabricated for the application of breast cancer therapy. This new therapeutic application not only reduces the significant side effect but also decreases the total dosages of anti-cancer drugs. Combing with magnetic resonance imaging techniques, the carriers can be easily tracked and therapeutic efficacy can be monitored in real time. We also anticipate that the technical information stemmed from this project will be technically, scientifically, and medically valuable as reference to provide potential curing clues for other cancer treatment. Reference 1. Shang-Hsiu Hu, Bang-Jie Liao, Chin-Sheng Chiang, Po-Jung Chen, I-Wei Chen, and San-Yuan Chen, Core-shell Nanocapsules Stabilized by Single-Component Polymer and Nanoparticles for Magneto-Chemotherapy-Hyperthermia with Multiple Drugs, Adv. Mater., 2012, 24, 3627. (IF=13.877, N/M=6/231=1.93%) 2. Shang-Hsiu Hu, San-Yuan Chen, and Xiaohu Gao, Multifunctional nanocapsules for simultaneous encapsulation of hydrophilic and hydrophobic compounds and on-demand release, ACS Nano, 2012, 6, 2558. (IF=10.774, N/M=9/231=3.9%) 3. Shang-Hsiu Hu, Wei-Lin Tung, Chen-Fu Liao, Dean-Mo Liu and San-Yuan Chen, Surfactant-free, “Surfactant-free, Self-Assemble PVA-Iron Oxide /Silica Core-Shell Nanocarriers for High-Sensitive Magnetically Controlled Drug Release and Ultra-high Cancer Cell Uptake Efficiency”, Adv. Func. Mat., 2008, 18, 2946-2955. (IF=10.179, N/M=10/222=4.50%, citation #23)
Development of Multifunctional Magnetic Nanocarriers Combined with Targeting and Magnetic Resonance Image for Enhanced Breast Tumor Therapy and Monitoring (I)
Keywords: 藥物載體; 氧化鐵; 乳癌; 標靶; Drug Carrier; Iron Oxide; Breast Cancer; Target